Health‐related quality of life among people who use methamphetamine. (30th May 2019) - McKetin, Rebecca; Voce, Alexandra; Burns, Richard; Shanahan, Marian
Abstract: Introduction and Aims: We assessed health‐related quality of life amongst people who use methamphetamine, examined how this related to different patterns of methamphetamine use and what other factors were associated with decrements in quality of life in this sample. Design and Methods: A cross‐sectional survey of 169 at least monthly methamphetamine users. Health utility scores were derived using the Assessment of Quality of Life – 4D for the past month (0 reflects death and 1 represents full health; the population mean Assessment of Quality of Life score in Australia is 0.81). Dependence on methamphetamine was a score of 4+ on the Severity of Dependence Scale. Other measures included days of methamphetamine use and other substance use in the past month, injecting methamphetamine, demographics, psychiatric symptoms (score of 4+ on the Brief Psychiatric Rating Scale items) and a lifetime DSM‐IV diagnosis of schizophrenia. Results: The mean utility score was 0.52 (95% confidence interval 0.48–0.56). Methamphetamine dependence was associated with lower utility (−0.10, P = 0.003) after adjustment for other univariate correlates of utility. Other factors independently associated with lower utility were being a woman (−0.14, P < 0.001), depression (−0.10, P = 0.008), self‐neglect (−0.08, P = 0.035), schizophrenia (−0.17, P = 0.003) and fewer years of schooling (0.02 per year, P = 0.037). Discussion and Conclusions: We found poor quality of life in this sample of methamphetamine users relative to the general population, this being associated with both dependence on methamphetamine and other factors, particularly poor mental health. We also found poorer health amongst women.